METABOLISME LIPID DALAM TUBUH - Fazidah Aguslina Siregar; Tri Makmur (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Lipids are a group of heterogeneous compounds related to fatty acids and are stored in the body as energy producers. Lipids consist of simple lipids (fats, waxes), lipid mixtures (phospholipids, glycolipids) and lipid derivatives (fatty acids, glycerol and steroids). Lipid As an important food element because in addition to having high energy, also because vitamins are fat soluble. Lipids affect the utilization of fat in the body. While fat functions as a heat insulator in subcutaneous tissue and an electrical insulator that allows rapid propagation of depolarization waves along the myelinated nerves. High fat content in nerve tissue. The combination of fat and protein (lipoprotein) is an important element and functions as a means of transporting lipids in the blood. Lipid metabolism consists of catabolism and anabolism, and includes triglyceride metabolism, cholesterol metabolism and lipoprotein metabolism. Abnormalities in lipid metabolism are the underlying cause of atherosclerosis which is a risk factor for coronary heart disease and stroke. Knowledge of the role and metabolism of lipids in health is important in understanding biomedical problems.